STUDY OF GENETIC VARIATION, HERITABILITY AND CORRELATION IN VEGETABLE PEA (PISUM SATIVUM L.) - POOJA PANDEY; NEERAJ SINGH; MONISHA RAWAT (The Bioscan, 2015)
Twenty six genotypes of garden pea were evaluated for magnitude of Genetic variability, heritability, genetic advance and correlation for eleven yield contributing traits at V.R.C., GBPUAT, Pantnagar, Uttarakhand. The phenotypic coefficient of variation (PCV) was invariably higher than their corresponding genotypic coefficient of variation (GCV) for most of the characters. High genotypic coefficient of variation (GCV) as well as phenotypic coefficient of variation (PCV) was observed for plant height (25.94 and 25.58), pod yield per plant (25.28 and 25.32), number of pods per plant (21.89 and 24.22) and pod yield per hectare (20.34 & 20.62). High heritability with high genetic advance in percent of mean was observed for plant height (99, 53.36), total soluble solids (99, 53.36) and pod yield per plant (99, 51.99), which indicate that these traits were under additive gene control and selection for genotypic and phenotypic improvement for these traits would be effective. Correlation studies revealed that significant association of yield per hectare with pod yield per plant (0.84, 0.82), total soluble solids (0.72, 0.70), number of pods per plant (0.74, 0.62), and days to 50% flowering (0.67, 0.65) at genotypic and phenotypic level (GCV and PCV) respectively.